Potential biomarker for early risk assessment of prostate cancer - Markushin, Y.; Gaikwad, N.; Zhang, H.; Kapke, P.; Rogan, E.G.; Cavalieri, E.L.; Trock, B.J.; Pavlovich, C.; Jankowiak, R. (The Prostate, 2006)
BACKGROUND Catechol estrogen quinones (CEQ) derived from 4‐hydroxyestrone (4‐OHE1) and 4‐hydroxyestradiol (4‐OHE2) react with DNA to form depurinating—N7Gua and—N3Ade adducts. This damage leads to mutations that can initiate breast and prostate cancer. To determine whether this damage occurs in humans, urine samples from men with prostate cancer and benign urological conditions, and healthy controls were analyzed. The objective was determining whether any of the cancer patients had formed the depurinating 4‐OHE1(E2)‐1‐N3Ade adducts. METHODS The adducts were extracted from samples by using affinity columns equipped with a monoclonal antibody developed for detecting 4‐OHE1(E2)‐1‐N3Ade adducts. Eluted extracts were separated by capillary electrophoresis with field‐amplified sample stacking and/or ultraperformance liquid chromatography. Absorption/luminescence spectroscopies and mass spectrometry were used to identify the adducts. RESULTS 4‐OHE1‐1‐N3Ade was detected at higher levels in samples from subjects with prostate cancer (n = 7) and benign urological conditions (n = 4) compared to healthy males (n = 5). CONCLUSION This is the first demonstration that CEQ‐derived DNA adducts are present in urine samples from subjects with prostate cancer. Prostate 66: 1565–1571, 2006. © 2006 Wiley‐Liss, Inc.